1986
DOI: 10.1037/0278-6133.5.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Social learning influences on menstrual symptoms and illness behavior.

Abstract: The contribution of learning to the adult experience of illness was investigated by asking 351 nursing students how their mothers reacted to menstrual symptoms and cold symptoms during their adolescence and how their mothers behaved when they themselves had menstrual symptoms. Mothers of respondents were independently asked the same questions. Nursing students who had been encouraged to adopt a sick role for menses or whose mothers modeled menstrual distress reported significantly more menstrual symptoms, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…According to operant and cognitive-behavioral models of chronic pain (e.g., Fordyce, 1976;Kerns et al, 1991;Turk et al, 1987), caregivers (including parents) provide discriminative cues and selective reinforcement for behavioral expressions of pain (e.g., complaints of pain, guarded movement). Parental attention contingent on pain, the avoidance of nonpreferred activities (Philips, 1987), and parental modeling influences (Whitehead, Busch, Heller, & Costa, 1986) may affect the child's pain. Specifically, some caregiving practices (e.g., sympathy and attention, expression of concerns, physical nurturance, external help seeking, or emotional reactions of anger or criticism) may reinforce pain behaviors (Fordyce, 1976;Payne & Norfleet, 1986).…”
mentioning
confidence: 99%
“…According to operant and cognitive-behavioral models of chronic pain (e.g., Fordyce, 1976;Kerns et al, 1991;Turk et al, 1987), caregivers (including parents) provide discriminative cues and selective reinforcement for behavioral expressions of pain (e.g., complaints of pain, guarded movement). Parental attention contingent on pain, the avoidance of nonpreferred activities (Philips, 1987), and parental modeling influences (Whitehead, Busch, Heller, & Costa, 1986) may affect the child's pain. Specifically, some caregiving practices (e.g., sympathy and attention, expression of concerns, physical nurturance, external help seeking, or emotional reactions of anger or criticism) may reinforce pain behaviors (Fordyce, 1976;Payne & Norfleet, 1986).…”
mentioning
confidence: 99%
“…Whitehead IBS-el kapcsolatos vizsgálatai, amiben telefonos felmérésre építve kimutatták, hogy az IBS-ben jellemző tüneteket a populáció kb. 20%-a jól ismeri, de csak 1% fordult ilyen tünetekkel valaha is orvoshoz Whitehead et al, 1986 . Szomatikus tüneteket egyébként a populáció 70-90 %-a mutat (pl.…”
Section: Kórképek éS Tünetekunclassified
“…Turkat [16] found evidence for the effect of modeling in diabetic patients, patients with chronic headaches [17] and in a small group of healthy subjects [18] . Several studies have interviewed adults about their experiences as children, and found higher reported rates of reinforcement and modeling for illness behavior during childhood among adults with Irritable Bowel Syndrome (IBS, a condition characterized by abdominal pain or discomfort and altered bowel habits occurring in the absence of underlying disease pathology) compared to asymptomatic control groups [15,[19][20][21] .…”
Section: Childhood Social Learning Effects On Adult Illness Behaviormentioning
confidence: 99%